تنفيذ الإعراب و البناء في تعليم علم النحو عند الدكتور إبراهيم مصطفى - Anwar, Khoirul (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
The grammarians say in the definition of grammar is a science known by the conditions of late speech and construction. In spite of this phrase, they limited the study of grammar to the last letter of the word and singled out the expression and construction. Then they do not mean much building and do not prolong the search in its provisions, but they make it important to explain the causes and causes. It is possible that this periodical offers new suggestions for knowledge of the materials of expression and construction in the teaching of grammar and the knowledge of the renewal of the grammar of Dr. Ibrahim Mustafa. The result is that Ibrahim Mustapha wants to teach grammar not for knowledge of changing the movements of the late words only, but because the students know the meanings of the words in the sentence by the knowledge of their last movements, so he shortens the doors of many grammar to three large sections, The addition and the opening is not a sign of expression and is not much discussed in construction because it is clear and does not change in different situations such as expression.